ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE GOVERNANCE PADA LAPORAN TAHUNAN (Studi Empiris pada Perusahaan yang Terdaftar dalam LQ-45 Bursa Efek Indonesia) - Natalia, Petri; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2012)
This study aims to analyze the factors that influence corporate governance disclosure in annual reports. The factors tested in this study are the independence of audit committees, firm size, profitability, leverage, and industry classification.Colleting data is using purposive sampling method to the companies listed in the LQ-45 Indonesian Stock Exchange during 2010-2011. A total of 78 companies in used as sample in this research. There are 93 items to detect broad disclosure of corporate governance disclosure.This research uses multiple regression were used to examine the factors that influence corporate governance disclosure. The results of this research showed that the independent variables that significantly affect the disclosure of corporate governance is the independence of the audit committee and industry classifications. However, firm size, profitability, leverage and showed no significant effect on corporate governance disclosure.